Pelatihan Teknik Penulisan Karya Tulis Ilmiah Bagi Mahasiswa - Asriani Ridzal, Dewi; Hartinawanti; Haswan; Hatuala, Mujuna (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Writing is part of the basic literacy that must have students face the challenges of the 21st century. Scientific work is writing that contains a review/study using scientific principles to discuss a particular problem. The students must understand very well the methodology for preparing scientific papers to produce the best scientific papers. Community service activities are carried out in the form of training with the theme of training in scientific writing techniques attended by FKIP students of Buton Muslim University totaling 30 participants from two study programs, namely Biology Education and Elementary School Teacher Education. Overall, the implementation of community service activities with the theme of training in scientific writing techniques went well and smoothly as expected. PKM activities show results that 90% of participants have a great understanding of scientific writing techniques, and 10% of participants are in enough category.